Advances in probiotic encapsulation methods to improve bioactivity. (April 2023) - Sun, Chenyuan; Wang, Shengnan; Yang, Lina; Song, Hong
Abstract: The health benefits of probiotics may not be fully realized because they are destroyed during food storage and digestion. This considerably reduces their biological activity, therefore preventing them from colonizing the gut and exerting their health advantages. The encapsulation of probiotics will considerably improve their oral availableness and biological activity whereas increasing viscus organisation rate and secretion adhesion. The encapsulation result of probiotics depends on the encapsulation methodology and material; Therefore, it is essential to select appropriate methods and materials. Currently, a series of capsule systems are developed to enhance the survival rate of probiotics reaching the colon. We tend to introduce many encapsulating strategies of probiotics, such as hydrogel technique, emulsification technique, electrospinning technology, biofilm self-encapsulation, and the tableting technique. In addition, we also describe their mechanism of action, which can improve probiotics' organisation ability within the viscus tract and enhancing health advantages within the physical body.